Dataset for performance of superior dairy cattle sires based on daughter's milk yield in tropical country - Prafangasti Sarah Ginantika; Didin Supriat Tasripin; Heni Indrijani; Dedi Ruswandi (Data in Brief, 2024)
Sire has an important role because they could have more offspring than dam does. The research aims to determine the production performance of Friesian Holstein, estimation of heritability values, estimation of breeding values, and ranking of dairy cattle sires. The objects of the study were the complete record of milk production, lactation length, lactation peak, and dry period length from first to fourth lactation from 2017-2021. This study used the descriptive method. The results of the research showed that productivity performance is great, 1st lactation milk production was 8,029.28±1,112 kg, the lactation length was 321.26±38.48 days, the condition of average peak production was obtained on day 85.35±29.25 with milk production of 32.55±4.16 kg, and dry period length was 51.37±9.33 days. 2nd Lactation milk production was 7,761.66±1,145, the lactation length was 323.66±43.06 days, the condition of average peak production was on day 58.43±21.11 with milk production of 40.79±5.30 kg and the dry period length was 65.10±22.69 days. 3rd lactation milk production 3 was 7,788.92±1,148 kg, the lactation length was 326.64±46.74 days, peak production was on day 61.88 ±22.72 with milk production of 43.62±5.11 kg; the dry period length was 65.00±20.49 days. 4th Lactation milk production was 7,484.18±1,133 kg, lactation length was 323.04±42.23 days, peak production was on day 66.39±24.26 with the milk production of 43.82±5.68, the dry period length was 65.78±21.60 days. The estimated heritability value for milk production, 0.03 ± 0.02, is included in the low category. The ranking of 10 sires that have the potential to increase the genetic based on their estimated breeding value is 595.91 kg (O.S.Elmer-XA), 264.16 kg (M.Z.Merlin.-XA), 252.38 kg (L.Muscadet-XA), 247 .12 kg (C.Toyjet), 239.01 kg (S. Gypsy B), 214.82 kg (WestCoastPldge), 188.14 kg (M.Z.Merlin-ET), 178.56 kg (Brasilia), 166.43 kg (L.JetBowser-XA), 162.06 kg (MRMUDD-XA).